Comprehensive case report and literature review on perioperative management of multiple pheochromocytoma in a pediatric patient - Yu, Shenghua; Zou, Tianxiao; Wei, Sisi; Yu, Yani; Ding, Guili (Frontiers in Pediatrics, 2025)
Pheochromocytomas (PCCs) are rare neuroendocrine tumors originating from the adrenal medulla, particularly uncommon in pediatric populations. This case report presents a 12-year-old boy with a three-year history of fatigue and a one-year history of blurred vision, who was admitted with severe hypertension (230/200 mmHg). Abdominal CT imaging revealed bilateral adrenal masses measuring 40 mm on the left and 12 mm on the right. The diagnosis of pheochromocytoma was confirmed by elevated blood catecholamine metabolites. During perioperative preparation, the patient experienced complications, including polyuria, thrombosis, and infection, necessitating an emergency resection of the right adrenal tumor. This intervention led to a successful recovery. Subsequent genetic testing identified a mutation in the VHL gene. After further medical management, the left adrenal tumor was also successfully removed. At one-year follow-up, the patient remained normotensive with no signs of recurrence. This case emphasizes the critical role of genetic testing and cutious perioperative management in the treatment of pediatric pheochromocytoma.